If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2m + (-6m) = 0 Combine like terms: -2m + (-6m) = -8m -8m = 0 Solving -8m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Divide each side by '-8'. m = 0 Simplifying m = 0
| 10x-1=9x+8 | | 8(y+3)=4Y+32 | | 4x+(-3x)= | | -16-5z=51 | | 8(7+3)=4y+32 | | (x-8x-20)=(x+2) | | 2.22-3.34x=2x-4.555 | | 5y+3-2y-1=25 | | 3x+7=-8x+2 | | 58x^2+40x=0 | | 1.2x=1.4 | | 6-2x=-5x-9+14 | | 24m-16n= | | a+(a-9)=(a-7)-(a+2) | | (X+9x+18)=(x+6) | | 8x-22=230-10x | | 11=-2 | | -2and-38=76 | | 24+8*x=3*x-4 | | -88=-8(1-3r) | | 3(x+5)-10=2(x+1) | | 3p+5=9p-7 | | 15=-p-2 | | 4-2k=-5k+35 | | 49=-7d | | (m+12)+2m+90=180 | | W*5+17=-3 | | (x+3)-2(2-4x)=3(x+4)-1 | | 5x+(x+24)=180 | | -4.9t^2+6t+70=0 | | 5(x+4)-2(7-2x)=2x+3 | | -4x+(-20)=12 |